Modifications premières de l’iode lié à la proteine, de l’iode extractible au butanol, du facteur de conversion et de l’iode radioactif lié à la proteine pendant le traitement au 131I de la thyréotoxicose et du cancer de la thyroïde - Bednář, J.; Němec, J.; Soutorová, M.; Röhling, S. (Nuklearmedizin - NuclearMedicine, 1969)
The interval after which damage of the thyroid following the administration of therapeutic doses of 131I is manifested by changes in the concentration of iodine substances in blood differs depending on the type of estimation, the type of thyroid disease, on individual radiosensitivity, the functional state of the thyroid and the amount of energy absorbed by the thyroid. Protein-bound iodine (PBI) and butanol-extractable iodine (BEI ) during therapy underwent different changes in individual patients but during the early period after administration (within five to six weeks), they did not change fundamentally in thyrotoxicoses. After thyroid ablation in cancer patients the declining trend of PBI was more marked following a temporary increase. A decline of the PBI and BEI concentration in blood occurs only after a certain period following 131I therapy. It was most marked in thyroid cancer where in the majority of patients controlled eight to twelve weeks following administration the PBI values were less than 4 μg% and the BEI concentration was very low or could not be detected at all. Interesting differences were manifested in the PB131I level in both sub-groups of hyperthyroid patients (metabolic and cardiac form) which may prove important from the diagnostic aspect. The explanation of the observed phenomena is discussed in detail.